(3QSGdI aj CMcGe GdChbGa ef GdGSJFLGQ hGdGSJHOGds
(3ChdgG (B:s
(3GdMeO ddg GdPj hba aj HgGA CdhgjJg s
(3BNQgG (B:s
(3hcGf ddUZjQ jLjH CLQ GdeKd UjfI ddhba hGdUZjQ GfJgi hdjcf BNQ eG ChQOfG aj gPg GdQSGdI GdeYLGdI JeJ HYhf Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B(9304) s
Keywords: (3Gdabg GdMfajs